2018
DOI: 10.7554/elife.36645
|View full text |Cite
|
Sign up to set email alerts
|

A novel pH-dependent membrane peptide that binds to EphA2 and inhibits cell migration

Abstract: Misregulation of the signaling axis formed by the receptor tyrosine kinase (RTK) EphA2 and its ligand, ephrinA1, causes aberrant cell-cell contacts that contribute to metastasis. Solid tumors are characterized by an acidic extracellular medium. We intend to take advantage of this tumor feature to design new molecules that specifically target tumors. We created a novel pH-dependent transmembrane peptide, TYPE7, by altering the sequence of the transmembrane domain of EphA2. TYPE7 is highly soluble and interacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 67 publications
8
61
0
Order By: Relevance
“…We focused specifically on the role of HNF1α in the development and progression of PDAC in hopes to apply this knowledge in the development of more targeted and effective treatments for this disease. We found that silencing HNF1α reduced the proliferative, migratory, invasive and colony forming capabilities of pancreatic cancer cells, consistent with previous research that has identified it as a novel oncogene in pancreatic cancer 10 . Thus, continued research into the role of HNF1α is worthy of further exploration.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…We focused specifically on the role of HNF1α in the development and progression of PDAC in hopes to apply this knowledge in the development of more targeted and effective treatments for this disease. We found that silencing HNF1α reduced the proliferative, migratory, invasive and colony forming capabilities of pancreatic cancer cells, consistent with previous research that has identified it as a novel oncogene in pancreatic cancer 10 . Thus, continued research into the role of HNF1α is worthy of further exploration.…”
Section: Introductionsupporting
confidence: 92%
“…Further, it also been shown that HNF1α significantly promoted pancreatic cancers by influencing fibroblast growth factor receptor 4 23 . Recently, it has been shown that HNF1α is a putative regulator of PDAC stem cell gene signature 10 . Further, it has also been demonstrated that HNF1α is required for tumor growth, tumorsphere formation, invasion and migration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TYPE7 is a pH-sensitive peptide derived from the transmembrane domain of its target. Inducing a pH drop leads to the translocation of the peptide to the plasma membrane where it binds EphA2, promotes its oligomerization, and activates its downstream signaling [120]. A subset of peptides also targets EphA intracellular domains including the Sterile Alpha Motif (SAM) of EphA2.…”
Section: Peptides and Soluble Epha/ephrin-amentioning
confidence: 99%